1995
DOI: 10.1017/s0022112095002229
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational investigations of hypersonic flow about compression ramps

Abstract: Comprehensive results of a joint experimental and computational study of the two-dimensional flow field over flat plate/compression ramp configurations at Mach 14 are presented. These geometries are aimed to simulate, in a simplified manner, the region around deflected control surfaces of hypersonic re-entry vehicles. The test cases considered cover a range of realistic flow conditions with Reynolds numbers to the hinge line varying between 4.5 × 105 and 2.6 × 106 (with a reference length taken as the distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 32 publications
5
36
0
Order By: Relevance
“…The flow passing a compression ramp is a classic example of shock-boundary layer interaction. Two-dimensional computational results of these configurations compare poorly with experimental data, specially when large regions of separated flows are present [1,28,37]. Generally, there is an under prediction of the heat transfer over the ramp and an over estimation of the extent of the separation bubble.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow passing a compression ramp is a classic example of shock-boundary layer interaction. Two-dimensional computational results of these configurations compare poorly with experimental data, specially when large regions of separated flows are present [1,28,37]. Generally, there is an under prediction of the heat transfer over the ramp and an over estimation of the extent of the separation bubble.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there is an under prediction of the heat transfer over the ramp and an over estimation of the extent of the separation bubble. These discrepancies have been associated with three-dimensional effects [10,29,32] and transition at reattachment [1,37]. In most of the experiments involving shock-boundary layer interaction at hypersonic speeds, significant spanwise heat transfer variations were reported [17,37,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulation of supersonic flow over a doublecompression ramp with finite span is a challenging topic not only because of the three-dimensional complexity [1][2][3][4], but also due to turbulent transition inside the separation bubble [5,6], and/or numerical difficulties [7]. In his study of shock-shock interactions between an oblique shock and a bow shock over a cylinder, Edney [8] identified six different types of shock-shock interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of this approach is the ogive-cylinder-flare model of Wideman et al 45 shown in figure 2. It is also recognised 29 , however, that an axisymmetric configuration cannot guarantee (time-averaged) two-dimensionality, in particular the formation of cellular (streamwise) structures or Goertler-type vortices especially once flow separation is involved 9,22,29,30,35,40 . Figure 3 shows a rearward-facing step separated flow, generated at the base of a sting-supported circular section cone and conducted in the Imperial College Gun Tunnel.…”
Section: Introductionmentioning
confidence: 99%